STUDI INTERAKSI OBAT PADA PENGOBATAN PASIEN STROKE YANG DISEBABKAN HIPERTENSI DI RSUP. Dr. WAHIDIN SUDIROHUSODO MAKASSAR - Hendra Herman (As-Syifaa Jurnal Farmasi, 2010)
This research concerning by means non-experimental with descriptive approach was to collect the data with retrospectively compared take from medical data then to search the drugs that interacting each other on strokes patient caused by hypertension at RSUP. DR. Wahidin Sudirohusodo in Makassar. The result of this research showed that strokes and hypertensions drug that interacting each other in 2007 and 2008 was the interaction between aspire and captopril where in 2007 was 48% and in 2008 was 54%, with pharmacokinetics interaction type is distributions interaction.Key Words : Drug Interacting, strokes, hypertensions.